Fabrication and characterization of high-performance polymer-based magnetoelectric DC Magnetic Field sensors devices - Reis, Sílvia (2017)
The development of a DC magnetic field sensor based on a magnetoelectric (ME) PVDF/Metglas composite is reported. The ME sensing composite has a resonance frequency close to 25.4 kHz, a linear response (r2=0.997) in the 0-2Oe DC magnetic field range and a maximum output voltage of 112 mV (related to a ME voltage coefficient α33 of ≈30 V.cm-1.Oe-1). By incorporating a charge amplifier, an AC-RMS converter and a microcontroller on chip peripheric analog to digital converter (ADC) the ME voltage response is not distorted, the linearity is maintained and the ME output voltage increases to 3.3V (α33effective=1000 V.cm-1.Oe-1). The sensing device, including the readout electronics, has maximum drift of 0.12 Oe with an average total drift of 0.04 Oe, with a sensitivity of 1.5 V.Oe-1 (15 kV.T-1) and a 70nT resolution. This features compares favourably with a reference Hall sensor that showed a maximum drift of 0.07 Oe and an average error of 0.16 Oe, 5 V.T-1 sensitivity and 2 μT resolution. Those features allied to the accurate measurement of the HDC fields in the 0-2 Oe range make this polymer-based device very attractive for applications such as Earth magnetic field sensing, digital compasses, navigation and magnetic field anomaly detectors, among others.